Plasmon resonance and heat generation in nanostructures. (11th March 2015) - Fang, Xiaoping; Deng, Youjun; Li, Jing
Abstract : In this paper, the photothermal effects of plasmon resonance are investigated. Metal nanoparticles efficiently generate heat in the presence of electromagnetic radiation. The process is strongly enhanced when a fixed frequency of the incident wave illuminates on nanoparticles such that plasmon resonance happens. We introduce the electromagnetic radiation model and show exactly how and when the plasmon resonance happens. We then construct the heat generation and transfer theory and derive the heat effect induced by plasmon resonance. Finally, the heat generation under plasmon resonance in a concentric nanoshell structure is considered specially, and excited result is obtained. Copyright © 2015 John Wiley & Sons, Ltd.